Through Drama to Dialogue. The Role of "Word" in the Arriving at Dialogue according to Ferdinand Ebner - Krzysztof Skorulski (Nicolaus Copernicus University in Toruń, 2018)
Dialogue philosophers who are realistic about their matter, pay more attention to the arriving at dialogue than to dialogue itself. We see such an attitude, among others, in the writings of Ferdinand Ebner and Józef Tischner. Dialogue is a target situation, while the road to it is long and uncertain - according to Tischner, it leads through drama. Ebner, on whom we focus here in particular, sees the matter as follows: The "I" communicate with "You" through word and love. If the dialogue fails, then one of these four elements simply lacks. Because of the lack of space for the analysis of all these elements, we will focus on the word here. So what must the word be for dialogue to be possible? Let us list such characteristics of the word as its "actuality", both factual and personal, transparency in relation to the presented reality, connection with love, creative power (generative or "only" maieutic) and much more. However, it is difficult to deterministically define the terms of dialogue saying: When I do this and this, dialogue will definitely succeed. There is always an element of freedom and grace, as well as hope.